Some Remarks on the Xth Congress of Czech Historians in Ostrava - Švaříčková-Slabáková, Radmila (Dějiny – teorie – kritika, 2011)
The author presents distinctively subjective observations on the Xth Congress of Czech Historians, which took place on September 14–16, 2011 in Ostrava. She evaluates its limitations and contributions, both in relation to previous congresses of Czech historians and in connection with current historiography abroad and its main methodological trends.